Boosting the Quality Factor of Low Impedance VHF Piezoelectric-on-Silicon Lateral Mode Resonators Using Etch Holes. (2016) - Tu, C.; Lee, J.E.-Y.
Abstract: We report a unique method of using etch-holes to greatly improve the unloaded quality factor ( Q u ) of VHF-band low impedance laterally vibrating AlN Thin-film Piezoelectric-on-Silicon (TPoS) MEMS resonators. We have validated the proposed method experimentally by applying it to fabricated devices with resonant frequencies of 105 MHz. Based on the experimental results of several fabricated samples, we show that the quality factors of the resonators consistently improve by almost four times using the proposed method. The experimental results are corroborated by finite-element (FE) simulations, which show that the holes re-distribute the strain energy in the resonator and suppress the movement in the supporting beam tethers. Less energy in the tethers leads to reduction of anchor loss and thus enhances Q u .